APPLICATION OF KLEIN-4 GROUP ON DOMINO CARD - Saragih, Asido; Purba, Santri Chintia (Universitas Sanata Dharma, 2020)
Klein-4 or Klein-V group is a group with four elements including identity. The binary operation on Klein-4 group will produce identitiy if operated to it self and produce another non-identity element if operated to another non-identity element. The focus of this paper is to explain the principle of Klein-4 group on Domino card and also find all complete possible elements. Domino card is a set of 28 cards which the surface of each card divided in two identic boxes contain combination of dots as pattern. The final part of this research is to find out all possible combination of cards which can be used as elements of a Klein-4 groups.